Predicting the distribution of Philippine Endemic fruit bats and potential refugia under climate change in Cebu - Damole, Julcee Mar D.; Flores, Mary Joyce L. (Cebu City, Cebu Department of Biology and Environmental Science, College of Science, University of the Philippines Cebu, 2022)
Fruit bats have a significant ecological role in maintaining a healthy ecosystem. However, due to the changing global climate, the future of different Philippine endemic fruit bat species in Cebu, Philippines is threatened. Model projections were generated through MaxEnt to predict the species distribution and locate potential climate change refugia for the fruit bats on the island. The occurrence records were provided by the BioMeS NICER project of Cebu Technological University (CTU) and the Global Biodiversity Information Facility (GBIF), while the environmental datasets were collected from the CHELSA database. The raw occurrence and environmental data were processed through the R and Quantum Geographic Information System (QGIS) by eliminating duplications and multicollinearity. The distributions of Ptenochirus jagori, Haplonycteris fischeri, and Nyctimene rabori in Cebu were projected under the current climatic scenario, and three Shared Socio-economic Pathways (SSP1 2.6, SSP3 7.0 and SSP5 8.5) for the years 2040, 2070 and 2100. Potentially suitable habitats were concentrated at the southern part of the island, away from highly urbanized areas. Areas outside the key biodiversity sites were also projected to have moderate to high levels of suitability. Suitable habitats of all species were projected to greatly decrease in the future. H. fischeri had the least projected distributions and suitable habitats but N. rabori was considered the most vulnerable among the three fruit bat species because of its endangered status. It is recommended that research efforts on the impacts of climate change on local biodiversity should be increased especially on a regional scale. Due to the limitations of the generated models, future studies should consider non-bioclimatic factors such as land use and also biotic interactions between species and their environment to generate more conclusive results.
Thesis (Bachelor of Science in Biology). University of the Philippines Cebu. June 2022.